From margins to mainstream : feminism and fictional modes in Italian women's writing, 1968-1990 - Lazzaro-Weis, Carol M., 1949- (Philadelphia : University of Pennsylvania Press, 1993)
Carol Lazzaro-Weiss studies the fiction of twenty-five contemporary Italian women writers. Arguing for a notion of gender and genre, she runs counter to many Anglo-American and French feminist theorists who contend that traditional genres cannot readily serve as vehicles for feminist expression.
Frontmatter -- Contents -- Acknowledgments -- Introduction -- Chapter 1. Feminism and Its Literary Discontents -- Chapter 2. Separatism in Literature and Politics -- Chapter 3. From Confession to Romance -- Chapter 4. The Female Bildungsroman -- Chapter 5. The Historical Novel: History as Female Subjectivity -- Chapter 6. Cherchez la femme: Feminism and the Giallo -- Chapter 7. Mainstreaming -- Bibliography -- Index
Includes bibliographical references (pages 201-215) and index.
Print version record.
JSTOR
Keywords: Italian fiction -- Women authors -- History and criticism; Italian fiction -- 20th century -- History and criticism; Feminism and literature -- Italy; Feminism in literature; Roman italien -- 20e siècle -- Histoire et critique; Féminisme dans la littérature.; LITERARY CRITICISM -- Feminist; Feminism and literature; Feminism in literature; Italian fiction; Italian fiction -- Women authors; Italy; 1900 - 1999; Criticism, interpretation, etc